Determination of Stature from Upper Arm Length in Medical Students - Shadan Navid; Tahmineh Mokhtari; Tahereh Alizamir; Ali Arabkheradmand; Gholamreza Hassanzadeh (Negah Institute for Scientific Communication, 2014)
Introduction: In order to make a dimensional proportion between human and equipment or environment, anthropometric data bank is essential. Anthropometry has an important role in industrial management and ergonomic design. This information is needed to be collected regularly in every society. The purpose of this study was to determine arm length to height ratio according to gender in adults, between ages 19-21 in students of Medical Sciences, Tehran. Methods: This cross-sectional investigation was performed on 100 students (50 males and 50 females) from Tehran University of Medical Sciences (aged 19-21 years). Participants were selected randomly and they didn't have any physical deformities or any previous history of trauma. Standing height (stature) and upper arm length (UAL) were measured for each subject. Measurements were performed in standard position. Results: The mean age of cases was 21±1.32 years. Mean age of male cases was 20±1.2 years and female cases was 21±1.81 years and there wasn't significant difference in the age of sex groups (P=0.219). A significant differences were observed in the height between the two sexes (P=0.0001, and Table 1). Also, there was a significant difference in the upper arm length of sex groups (P=0.0001). In addition, there was a correlation between height and upper arm length of cases (r =0.716, P=0.0001). Conclusion: According to the results, UAL can be a reliable factor for predicting the stature in Iranian medical students.